Scale: Discourse and Dimensions of Social Life - Lempert, Michael; Summerson Carr, E. (University of California Press, 2016)
"Wherever we turn, we see diverse things scaled for us, from cities to economies, from history to love. We know scale by many names and through many familiar antinomies: local and global, micro and macro events. Even the most critical among us often proceed with our analysis as if such scales were the ready-made platforms of social life, rather than asking how, why, and to what effect are scalar distinctions forged in the first place. How do scalar distinctions help actors and analysts alike make sense of and navigate their social worlds? What do these distinctions reveal and what do they conceal? How are scales construed and what effects do they have on the way those who abide by them think and act? This pathbreaking volume attends to the practical labor of scale-making and the communicative practices this labor requires. From an ethnographic perspective, the authors demonstrate that scale is practice and process before it becomes product, whether in the work of projecting the commons, claiming access to the big picture, or scaling the seriousness of a crime."